2021
DOI: 10.1155/2021/6959557
|View full text |Cite|
|
Sign up to set email alerts
|

lncENST Suppress the Warburg Effect Regulating the Tumor Progress by the Nkx2-5/ErbB2 Axis in Hepatocellular Carcinoma

Abstract: The therapeutic efficacy of radiofrequency ablation (RFA) against liver cancer is often limited by proliferation and metastasis of residual tumor cells. These phenomena are closely associated with the Warburg effect, wherein ErbB2 is activated. While RFA inhibits the Warburg effect of residual tumor cells at the early stage, the specific mechanisms remain unclear. We explored the regulatory relationship between the long noncoding RNA ENST00000570843.1 (lncENST) and ErbB2 using lentiviral transfection of lncENS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Inhibiting the Warburg effect in HCC cells, lncENST directly binds to and activates the transcription factor Nkx2-5 through an Nkx2-5/ErbB2 axis. This inhibits ErbB2 gene transcription and downregulates ErbB2 protein expression (38). HOX transcript antisense RNA (HOTAIR) regulates a miR-130a-3p/HIF1A axis on miR-130a-3p uptake, resulting in high expression of HIF1A, which inhibits glycolysis in hypoxia-induced HCC cells (63).…”
Section: The Role Of Lncrna and Glucose Metabolism In Gastric Cancer ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting the Warburg effect in HCC cells, lncENST directly binds to and activates the transcription factor Nkx2-5 through an Nkx2-5/ErbB2 axis. This inhibits ErbB2 gene transcription and downregulates ErbB2 protein expression (38). HOX transcript antisense RNA (HOTAIR) regulates a miR-130a-3p/HIF1A axis on miR-130a-3p uptake, resulting in high expression of HIF1A, which inhibits glycolysis in hypoxia-induced HCC cells (63).…”
Section: The Role Of Lncrna and Glucose Metabolism In Gastric Cancer ...mentioning
confidence: 99%
“…1, it was found that lncRNAs, including protein tyrosine phosphatase receptor type G antisense RNA 1 (PTPRG-AS1) (31), H19 (32), MIR210 host gene (MIR210HG) (33), MIR17HG (29), LINC00243 (34), and LINC00346 (35), promote the growth of tumor cells, altering the expression of key gluconeogenesis enzymes through sponging of miRNAs. Additionally, several signaling molecules are regulated by lncRNAs, such as transmembrane protein 161B antisense RNA 1 (TMEM161B-AS1) (36), high expression in hepatocellular carcinoma (HEIH) (37), lncENST (38), and LINC00261 (28), that can affect glycolysis and tumor cell activity (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%